Puberty and fertility in classic galactosemia. Issue 2 (February 2021) - Flechtner, Isabelle; Viaud, Magali; Kariyawasam, Dulanjalee; Perrissin-Fabert, Marie; Bidet, Maud; Bachelot, Anne; Touraine, Philippe; Labrune, Philippe; de Lonlay, Pascale; Polak, Michel
Abstract : Classic galactosemia is a rare inborn error of galactose metabolism with a birth prevalence of about 1/30, 000–60, 000. Long-term complications occurring despite dietary treatment consist of premature ovarian insufficiency (POI) and neurodevelopmental impairments. We performed with the French Reference Centers for Rare Diseases a multisite collaborative questionnaire survey for classic galactosemic patients. Its primary objective was to assess their puberty, pregnancy, gonadotropic axis, and pelvic morphology by ultrasound. The secondary objective was to determine predictive factors for pregnancy without oocyte donation. Completed questionnaires from 103 patients, 56 females (median age, 19 years (3–52 years)) and 47 males (median age, 19 years (3–45 years)), were analyzed. Among the 43 females older than 13 years old, mean age for breast development first stage was 13.8 years; spontaneous menarche occurred in 21/31 females at a mean age of 14.6 years. In these 21 women, 62% had spaniomenorrhea and 7/17 older than 30 years had amenorrhea. All age-groups confounded, FSH was above reference range for 65.7% of the patients, anti-Müllerian hormone and inhibin B were undetectable, and the ovaries were small with few or no follicles detected. Among the 5 females who sought to conceive, 4 had pregnancies. Among the 47 males, 1 had cryptorchidism, all have normal testicular function and none had a desire to conceive children. Thus, spontaneous puberty and POI are both common in this population. Spontaneous menarche seems to be the best predictive factor for successful spontaneous pregnancy.